Lack of Renal Tubular Glucocorticoid Receptor Decreases the Thiazide-Sensitive Na+/Cl– Cotransporter NCC and Transiently Affects Sodium Handling - Canonica, Jérémie; Frateschi, Simona; Boscardin, Emilie; Ebering, Anna; Sergi, Chloé; Jäger, Yannick; Peyrollaz, Thibaud; Mérillat, Anne-Marie; Maillard, Marc; Klusonova, Petra; Odermatt, Alex; Koesters, Robert; et al. (Frontiers in Physiology, 2019)
Chronic glucocorticoid infusion impairs NCC activity and induces a non-dipping profile in mice, suggesting that glucocorticoids are essential for daily blood pressure variations. In this paper, we studied mice lacking the renal tubular glucocorticoid receptor (GR) in adulthood (GR knockouts, Nr3c1Pax8/LC1). Upon standard salt diet, Nr3c1Pax8/LC1 mice grow normally, but show reduced NCC activity despite normal plasma aldosterone levels. Following diet switch to low sodium, Nr3c1Pax8/LC1 mice exhibit a transient but significant reduction in the activity of NCC and expression of NHE3 and NKCC2 accompanied by significant increased Spak activity. This is followed by transiently increased urinary sodium excretion and higher plasma aldosterone concentrations. Plasma corticosterone levels and 11βHSD2 mRNA expression and activity in the whole kidney remain unchanged. High salt diet does not affect whole body Na+ and/or K+ balance and NCC activity is not reduced, but leads to a significant increase in diastolic blood pressure dipping in Nr3c1Pax8/LC1 mice. When high sodium treatment is followed by 48 hours of darkness, NCC abundance is reduced in knockout mice although activity is not different. Our data show that upon Na+ restriction renal tubular GR-deficiency transiently affects Na+ handling and transport pathways. Overall, upon standard, low Na+ and high Na+ diet exposure Na+ and K+ balance is maintained as evidenced by normal plasma and urinary Na+ and K+ and aldosterone concentrations.